RELOKASI HIPOSENTER GEMPABUMI MENGGUNAKAN METODE MODIFIED JOINT HYPOCENTER DETERMINATION (MJHD) UNTUK ANALISIS ZONA SUBDUKSI SUMATERA BAGIAN SELATAN - Deswita Sari; Fadiah Khairina; Gatut Daniarsyad (Jurnal Geofisika Eksplorasi, 2018)
The part of south Sumatera is very vulnerable region in case of earthquake disaster caused by convergent boundary of two tectonic plates Indo-Australian Plates and Eurasian Plates. Precise hypocenter analysis is needed to understand about  the accurate tectonic setting such as subduction zone in the area. Hypocenter relocation is used to recalculate earthquake hypocenter to become more accurate. To produce a more accurate hyposenter this hyposenter relocation is done by using the method of Modified Joint Hypocenter Determination (MJHD). Relocation using the Modified Joint Hypocenter Determination (MJHD) method uses IASP91 wave velocity which assumes that the inner structures are heterogeneous. In this study, used data P-wave and S-wave  arrival time in the period January 2010 s.d December 2016 with coordinates -3.5º s.d -9º LS - 99º s.d 106.5º BT. The results of the relocation using MJHD showed a change of earthquake hypocenter shown by RMS (Root Mean Square) value ranging from 0.2 s.d 0.5. There are three subduction of the part in south sumatra. The subduction zone formed in Bengkulu is about 26.78º, the subduction zone of Lampung is around 30.225º and the subduction of the Sunda Strait is about 52.53º. Subduction zone of Bengkulu at depth of 250 km, Lampung and Sunda Strait at depth 400 km.